Avaliação do potencial anti-inflamatório, anticoagulante e hemorrágico de heparinóides presentes em "Artemia franciscana" - Moura, Celton Pereira de (2004)
Heparan sulfate (HS) and Heparin (Hep) glycosaminoglycans (GAGs) are heterogeneous and highly charged polysaccharides. HS is structurally related to Hep but is much less substituted with sulfo groups than heparin and has a more varied structure (or sequence). Because of structural similiarities between these two polymers, they have been described together as heparinoids . Both chains bind a variety of proteins and mediate various physiologically important processes including, blood coagulation, cell adhesion and growth factor regulation. Heparinoids with structural characteristics similar to these described from HS and/or Hep from mammalian tissues have been isolated from different species of invertebrates, although only a few heparinoids from unusual sources have been characterized. The present study describes the presence of unusual heparinoids population from Artemia franciscana, isolated after proteolysis and fractionation by ion exchange resin and named, F-3.0M. The study model in vivo were hemostasis (rat tail scarification) and inflamatoty activity. The tests in vitro were used for coagulations assays (PT and APTT). The analyse of the heparinoids eluted with 3,0M NaCl showed electrophoretic migration in different buffer systems a single band with a behaviour intermediate between those of mammalian HEP and HS. The main products obtained from Artemia heparinoids after enzymatic degradation with heparitinases I and II from F. heparinum were N-sulphated disaccharides (∆U-GlcNS,6S/ ∆U,2S-GlcNS and ∆U-GlcNS) and N-acetylated disaccharides (∆U, GlcNAc). This heparinoid had a lower hemorrhagic effect (400μg/ml) when compared to unfractiionated heparins(25μg/ml).The results also suggest a negligible APTT activity of this heparinoid (62.2s). No action was observed on PT indicating that F-3.0M haven t action on the extrinsic pathway. The results showed that the fraction F- 3.0M have inhibitory effect on migration of leukocytes, 64.5% in the concentration of 10 μg/ml (P<0.001). The search for new heparin and/or heparan sulphates analogs devoid of anticoagulant activity is an atractive alternative and may open up a wide variety of new therapeutic applications